Metacognitive Abilities as a Protective Factor for the Occurrence of Psychotic-Like Experiences in a Non-clinical Population - Giugliano, Marco; Contrada, Claudio; Foglia, Ludovica; Francese, Francesca; Romano, Roberta; Dello Iacono, Marilena; Di Fausto, Eleonora; Esposito, Mariateresa; Azzara, Carla; Bilotta, Elena; Carcione, Antonino; Nicolò, Giuseppe (Frontiers in Psychology, 2022)
Psychotic-like experiences (PLEs) are a phenomenon that occurs in the general population experiencing delusional thoughts and hallucinations without being in a clinical condition. PLEs involve erroneous attributions of inner cognitive events to the external environment and the presence of intrusive thoughts influenced by dysfunctional beliefs; for these reasons, the role played by metacognition has been largely studied. This study investigates PLEs in a non-clinical population and discriminating factors involved in this kind of experience, among which metacognition, as well as psychopathological features, seems to have a crucial role. The aim of this study was to extend the knowledge about the relationship between metacognition, psychopathology, and PLEs, orienting the focus on metacognitive functioning. The sample consisted of 207 Italian participants (men = 32% and women = 68%) voluntarily recruited online, who gave consent to participate in the study. The average age of the sample was 32.69 years (SD: 9.63; range: 18–71). Subjects affected by psychosis, neurological disease, and drug addiction were excluded from the analyses. The following scales were used to investigate PLEs: Peters et al. Delusions Inventory (PDI), Launay-Slade Hallucinations Scale-Extended Revised (LSHSE), Prodromal Questionnaire-Brief (PQ-B), and Revised Hallucination Scale (RHS). To assess general psychopathological features, the Behavior and Symptom Identification Scale (BASIS-32) was administrated. The Metacognition Self-Assessment Scale (MSAS) was chosen to evaluate metacognitive functioning. From hierarchical regression analyses, it emerged that the presence of anxiety, depression, and impulsive/addictive symptoms constitute a remarkable vulnerability factor for PLEs, in line with previous evidence regarding the relationship between general psychopathology and PLEs. Metacognition negatively predicts PLEs, and its presence does not affect the significance of psychopathological variables, suggesting that metacognitive abilities seem to play a protective role for the occurrence of PLEs among non-clinical individuals, and such ability operates as an independent predictor along with other variables. These results are explained by the role of metacognitive functions, which allow individuals to operate many mental processes such as interpreting sensorial events as real or illusory, understanding behaviors, thoughts, and drives of others, and questioning the subjective interpretation of facts.